Change Detection for the Study of Object and Location Memory - Elmore, L. Caitlin (Behav Processes, 2012)
Six adult human participants were tested in change detection tasks for object and location memory with large and small sets of four different stimulus types. Blocked tests demonstrated that participants performed similarly in separate object and location tests with matched parameters and displays. In mixed tests, participants were informed that they would be tested with either object changes or location changes; surprisingly, they were nearly as accurate remembering both objects and locations as when either was tested alone. By contrast, in the large-set condition, performance was lower than baseline on surprise probe test trials in which participants were tested (on 13% of trials) with the change type opposite to the present block (e.g. location probe trials during the object change block). These probe-test results were further supported by the reduction in probe-baseline differences when tested with small sets (6) of these item types. Small sets required remembering locations and objects to resolve object-location confounds. Together these results show that humans can remember both objects and locations with little loss of accuracy when instructed to do so, but do not learn these contextual associations without instruction.